The Marketing Activities of Cultural Institutions as a Response to the Development of Streaming Platforms and the Virtualisation of Cultural Participation - Sobocińska, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: To show trends and new challenges for the marketing of cultural institutions in the context of virtualising cultural participation and the development of streaming platforms.Research Design & Methods: The paper shows trends and new challenges for the marketing of cultural institutions seeking to virtualise cultural participation and develop streaming platforms. The research procedure triangulates quantitative and qualitative research methods. It included literature studies, an analysis of the results of a survey conducted in 2022 on a sample of 1,019 Poles, and semiotic analyses.Findings: The values obtained from watching films in a cultural institution – for example, the cinema, is different from those streaming platforms offer their users. Watching movies via streaming platforms does not fully replace watching movies in cinemas, because it creates a completely different context for the reception of the artwork.Implications / Recommendations: The considerations presented in the paper indicate that virtualisation and hybridity in the sphere of culture should not so much mean transferring directly developed solutions to the Internet, but rather creating new, innovative ones, referring to the language of new media. At the same time, the hybrid nature of cultural events – their being provided now through classic and online means – strengthens both the events themselves and the value they offer consumers.Contribution: The main contribution is a presentation of the correlations between the perception of participation in culture and the reasons for giving up going to the cinema.